Effect of active immunization against GnRH‐I on the reproductive function in cat. (19th January 2015) - Jiang, Shudong; Hong, Meizhen; Su, Shiping; Song, Min; Tian, Yuan; Cui, Pei; Song, Shuang; Wang, Yaoyao; Li, Fubao; Fang, Fugui
Abstract This study was designed to explore the effect of active immunization against maltose binding protein‐gonadotropin releasing hormone I hexamer (MBP‐GnRH‐I6) on the reproductive function in cats. Each immunized cat was administered twice intramuscularly in the neck at 16 and 20 weeks old. The concentrations of the testosterone and estradiol and the level of anti‐GnRH‐I antibody in the serum were measured by radioimmunoassay and ELISA, respectively. The results showed that the weight and size of testicles and ovaries, and the concentrations of serum testosterone and estradiol in the immunized animals were lower than those of the control cats (P < 0.05), but that the levels of anti‐GnRH‐I antibody were significant higher compared to control animals (P < 0.05). Testicular tissues from the immunized male cats showed that seminiferous tubules were depauperate with the lumen relatively empty and that the differentiation of spermatogonia was not obvious. Tissues from the immunized female cats showed that the ovaries had many primordial follicles and primary follicles, but no secondary follicle was observed. These results showed active immunization against MBP–GnRH‐I6 could make the gonads atrophy and reduce the concentrations of gonadal hormones, which suggested that MBP‐GnRH‐I6 was a very effective immunogen in the cat.